Proceso de atención de enfermería en adultos mayores con diagnóstico de neumonía adquirida en la comunidad en el área de medicina interna del Hospital Alfredo Noboa Montenegro. - Atiencia Zurita, Kasandra Micheld (2020)
The present case study that has been developed deals with the nursing care process in a 71-year-old patient with a medical diagnosis of Pneumonia Acquired in the Community, which is admitted to the internal medicine area of the Alfredo Noboa Hospital Montenegro. There are several risk factors associated with this complication, such as Diabetes mellitus, which weakens the immune system, together with the advanced age of the patient, which generates very unstable conditions and high risk for the restoration of her health. The objective of this case study is centered on comfort care, pain management, and improving the quality of lifestyles during hospital stay based on the theory of the 13 functional patterns of Marjory Gordon to achieve adequate access to the patient and to carry out the nursing activities based on the taxonomy Nanda, NIC and NOC. The NAC is not a simple management process. Establishing the etiological diagnosis and performing an appropriate antibiotic treatment is often a complicated task. For these reasons, we will make the diagnosis based on the grouping of clinical, analytical, radiological and epidemiological criteria. In this way we can establish a rational treatment, avoiding the unnecessary use of antibiotics. And achieving the effective treatment to shorten the stay of the hospitalized patient which would reduce expenses and adaptability to the patient. (A. Méndez Echevarría, 2008)